Forcing migration of globalised citizens - Gómez, O (Refugee Studies Centre, University of Oxford, 2014)
Today’s constant flows of persons and information across frontiers mean that, when an emergency occurs, the international community feels it has to get involved not only out of solidarity but because its citizens could be in danger.